Identifikasi Tipe Trikoma dan Stomata pada Tumbuhan Famili Myrtaceae - Sinaga, Fnesia; Purba, Fransiska; Kembaren, Gita Br.; Sinaga, Florenita; Kasih, Indah; Simanjuntak, Helen Anjelina (Herbal Medicine Journal, 2024)
The Myrtaceae family is a group of flowering plants that includes various species known for having certain characteristics, such as aromatic leaves, flowers with many stamens, and varied fruits. This is supported by the characteristics of the structure of the stomata and trichomes. This study aims to determine the characteristics of the stomata and trichomes of five species of the Myrtaceae family that grow in the environment that is often found. The five species are guava (Psidium guajava), clove (Syzygium aromaticum), water apple (Szygium aqueum), nutmeg (Myristica fragrans), and red tip tree (Syzygium myrtifolium). Leaf epidermis anatomical preparations were made using the paradermal section method. The results showed that the characteristics of the stomata of the five species are parasitic, diacytic, and anomocytic stoma types. In the five species that have trichomes is the guava plant (Psidium guajava) which is multicellular and non-glandular.